Decreased capsaicin cough reflex sensitivity predicts hospitalisation due to COPD. Issue 1 (25th January 2023) - Kanemitsu, Yoshihiro; Kurokawa, Ryota; Akamatsu, Taisuke; Fukumitsu, Kensuke; Fukuda, Satoshi; Ito, Yutaka; Takeda, Norihisa; Nishiyama, Hirono; Ito, Keima; Tajiri, Tomoko; Mori, Yuta; Uemura, Takehiro; et al.
Abstract : Introduction: Patients with chronic obstructive pulmonary disease (COPD) are often hospitalised due to severe acute exacerbation (AE) or community-acquired pneumonia (CAP). Previous studies revealed the association of cough reflex sensitivity with the pathophysiology of COPD and pneumonia. We hypothesised that cough reflex sensitivity may be associated with severe AE or CAP requiring hospitalisation in patients with COPD. Methods: We prospectively recruited 68 patients with COPD between June 2018 and January 2020. Patient characteristics, lung and cardiac functions, and biomarkers, including capsaicin cough reflex sensitivity and blood eosinophil count, were evaluated at enrolment. All participants were monitored for AE or CAP requiring hospitalisation for 12 months. We determined the risk factors and ORs for hospitalisation in patients with COPD using a multivariate analysis. Results: Eight patients experienced AE (n=3) or CAP (n=5) and required hospitalisation during follow-up. Patients in the hospitalisation+ group had higher modified Medical Research Council scores and blood eosinophil counts (≥300 µL) than those in the hospitalisation− group. Capsaicin cough reflex sensitivity tended to decrease in the hospitalisation+ group compared with that in the hospitalisation− group. Multivariate analysis revealed that a decreased capsaicin cough reflex and high eosinophil count (≥300 µL) were predictive risk factors for future hospitalisation due to AE-COPD or CAP. Conclusion: In addition to eosinophils, decreased capsaicin cough reflex sensitivity was associated with hospitalisation due to AE-COPD or CAP. Capsaicin cough reflex sensitivity in patients with COPD may play a role in the prevention of severe AE or pneumonia requiring hospitalisation. Trial registration number: UMIN000032497.